A educação física e o professor diante da questão da obesidade infantil - CORRÊA, Vanessa Bernardes Gomes (2019)
Obesity is currently one of the major public health problems in Brazil and the world, which is now considered by the World Health Organization (WHO) as a global epidemic. This disease is increasingly present in Brazilian families, which follow the tendencies of the globalization process, opting for the consumption of industrialized, high caloric and easily prepared foods. It should be emphasized that the sedentary lifestyle has a significant portion of responsibility, thus contributing to the spread of this epidemic. From this perspective, it is problematic: what is the role of Physical Education and Physical Education teacher in face of childhood obesity? To answer this question, the general objective was to understand the role of Physical Education and Physical Education teacher in the face of childhood obesity. As for the specifics, it was delimited: a) to contextualize obesity historically; b) characterize childhood obesity; and c) evidence the contributions of Physical Education and the Physical Education teacher regarding the issue of childhood obesity. The methodology used was a bibliographic study based on authors who discuss obesity and childhood obesity, as well as scholars in the area of Physical Education. In this study, it was noted that physical education teacher can contribute to combat this evil, and may help in the fight against childhood obesity, through knowledge related to various body practices that can help in the acquisition of a healthy lifestyle, unfortunately, today most children have only the small spaces in their homes and the school environment to practice some physical activity.